Physiological Characterization of a Plant Mitochondrial Calcium Uniporter in Vitro and in Vivo. Issue 2 (28th December 2016) - Teardo, Enrico; Carraretto, Luca; Wagner, Stephan; Formentin, Elide; Behera, Smrutisanjita; De Bortoli, Sara; Larosa, Véronique; Fuchs, Philippe; Lo Schiavo, Fiorella; Raffaello, Anna; Rizzuto, Rosario; Costa, Alex; et al.
Abstract : An Arabidopsis homolog of the mammalian mitochondrial calcium uniporter MCU acts as Ca 2+ channel, and its absence impacts mitochondrial function and morphology. Abstract: Over the recent years, several proteins that make up the mitochondrial calcium uniporter complex (MCUC) mediating Ca 2+ uptake into the mitochondrial matrix have been identified in mammals, including the channel-forming protein MCU. Although six MCU gene homologs are conserved in the model plant Arabidopsis ( Arabidopsis thaliana ) in which mitochondria can accumulate Ca 2+, a functional characterization of plant MCU homologs has been lacking. Using electrophysiology, we show that one isoform, AtMCU1, gives rise to a Ca 2+ -permeable channel activity that can be observed even in the absence of accessory proteins implicated in the formation of the active mammalian channel. Furthermore, we provide direct evidence that AtMCU1 activity is sensitive to the mitochondrial calcium uniporter inhibitors Ruthenium Red and Gd 3+, as well as to the Arabidopsis protein MICU, a regulatory MCUC component. AtMCU1 is prevalently expressed in roots, localizes to mitochondria, and its absence causes mild changes in Ca 2+ dynamics as assessed by in vivo measurements in Arabidopsis root tips. Plants either lacking or overexpressing AtMCU1 display root mitochondria with altered ultrastructure and show shorter primary roots under restrictive growth conditions. In summary, our work adds evolutionary depth to the investigation of mitochondrial Ca 2+ transport, indicates that AtMCU1, together with MICU as a regulator, represents a functional configuration of the plant mitochondrial Ca 2+ uptake complex with differences to the mammalian MCUC, and identifies a new player of the intracellular Ca 2+ regulation network in plants.